2003
DOI: 10.1046/j.1523-1755.2003.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein is associated with renal function abnormalities in a non-diabetic population

Abstract: As in cardiovascular disease, CRP appears to be a risk marker for renal function loss. The mechanism of this relationship remains to be clarified. However, the association between CRP, body weight, and a relatively elevated creatinine clearance is a hypothesis-generating finding, suggesting that early inflammatory processes related to high body fat may predispose the kidney to glomerular hyperfiltration-related renal function loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
148
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 44 publications
(6 reference statements)
19
148
2
Order By: Relevance
“…Renal insufficiency, a condition whereby endothelial dysfunction is pervasive (22), very frequently is accompanied by raised CRP. CRP was found recently to be associated with a subtle reduction in creatinine clearance in the Prevention of Renal and Vascular Endstage Disease (PREVEND) study (23). In keeping with these observations, we reported that CRP was related inversely both with the vasodilatory response to ACh and with renal function.…”
Section: Discussionsupporting
confidence: 88%
“…Renal insufficiency, a condition whereby endothelial dysfunction is pervasive (22), very frequently is accompanied by raised CRP. CRP was found recently to be associated with a subtle reduction in creatinine clearance in the Prevention of Renal and Vascular Endstage Disease (PREVEND) study (23). In keeping with these observations, we reported that CRP was related inversely both with the vasodilatory response to ACh and with renal function.…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate linear regression analysis was used to investigate the cross-sectional relations between WHR and BMI, respectively, with renal hemodynamics, with adjustment for sex, age and MAP. In line with general population studies using creatinine clearance or eGFR, 59 the relation of age with GFR was nonlinear and was better described with addition of a quadratic term of age in the regression models. To test whether effects of WHR on renal hemodynamics were independent of BMI, the latter was forced into the model that tested the effects of WHR.…”
Section: Statistical Analysesmentioning
confidence: 58%
“…22 We similarly showed that higher quartiles of CRP levels are associated with a higher relative risk of impaired glomerular filtration, after adjustment for other factors associated with a raised CRP level. 23 …”
Section: The Mechanism Of Obesity-induced Renal Damagementioning
confidence: 99%